Laju Sedimentasi Di Perairan Ekosistem Terumbu Karang Kampung Yakore Distrik Demta Kabupaten Jayapura - Laura Nikita; Yunus Pajanjan Paulangan; Baigo Hamuna (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Sedimentation can be one of the factors that limit coral life because it can cover coral polyps, in high numbers it can even cause coral death. The purpose of this study was to determine the rate of sedimentation in the coral reef ecosystem and to determine the condition of coral reef cover in the waters of Kampung Yakore. This research was carried out from January to May 2021. The method used in this study was to collect sediment in a sediment trap for 14 days and the LIT (Line Intercept Transect) method to observe the condition of live coral cover. Data were collected at 3 stations at a depth of 3 m and 5 m. The results showed that the sedimentation rate in the waters of Kampung Yakore was moderate to very heavy where the highest sedimentation rate was at station 3 with a depth of 5 m. The sedimentation rate ranged from 30.28 – 67.74 mg/cm²/day at a depth of 3 m. Meanwhile, at a depth of 5 m, the sedimentation rate ranged from 68.30 – 133.21 mg/cm²/day. This shows that the sedimentation rate in the waters of Kampung Yakore is at a very heavy impact level. It is suspected that the high sedimentation rate is caused by the time when data collection is carried out during the rainy season so that the river discharge is getting bigger and carrying sediment to the sea. The percentage of live coral cover in the waters of Kampung Yakore was classified as "moderate" to "good" with percentages ranging from 39.28% - 71.76% at a depth of 3 m and ranging from 30.7% - 56.12% at a depth of 5 m. The highest percentage of the cover was at station 2 with a depth of 3 m, which was 71.76%.Key Words: Sedimentation Rate; Coral Reef Ecosystem; Coral Cover; Yakore VIllage